2014
DOI: 10.1186/1756-0500-7-677
|View full text |Cite
|
Sign up to set email alerts
|

Fungal keratitis caused by Beauveria bassiana: drug and temperature sensitivity profiles: a case report

Abstract: BackgroundBeauveria bassiana is an entomopathogenic fungus and is a rare cause of keratitis. We present a case of fungal keratitis caused by B. bassiana that was diagnosed by in vivo confocal microscopy and in vitro corneal cultures. In addition, we determined the temperature- and drug-sensitivities of the isolated strain of B. bassiana.Case presentationA 59-year-old Japanese man with a 2-month history of keratitis was examined by slit-lamp biomicroscopy, in vivo confocal microscopy, and histology and cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…[ 12 ], Acremonium spp. [ 13 ], Cryptococcus albidus [ 14 ]), Pythium insidiosum [ 15 ], Beauveria bassiana [ 16 ], Paecilomyces [ 17 ], Cunninghamella spinosum [ 18 ], Scedosporium apiospermum [ 19 ]), Rhodotorula mucilaginosa [ 20 ], Cylindrocarpon lichenicola [ 21 ], Cladorrhinum bulbillosum [ 22 ]. Lophotrichus species were isolated from the necrotic corneal sample complicating fungal keratitis after dog paw traumatic injury [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ], Acremonium spp. [ 13 ], Cryptococcus albidus [ 14 ]), Pythium insidiosum [ 15 ], Beauveria bassiana [ 16 ], Paecilomyces [ 17 ], Cunninghamella spinosum [ 18 ], Scedosporium apiospermum [ 19 ]), Rhodotorula mucilaginosa [ 20 ], Cylindrocarpon lichenicola [ 21 ], Cladorrhinum bulbillosum [ 22 ]. Lophotrichus species were isolated from the necrotic corneal sample complicating fungal keratitis after dog paw traumatic injury [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Histopathologically, B. bassiana grows slowly in corneal cells [12], and it generally does not invade the anterior chamber which, according to some authors, may be due to its inability to grow at 35-37°C [10]. In the case reported, B. bassiana did invade the anterior chamber, which might be the result of a reactive uveitis caused by an existing epithelial lesion or by the concomitance of two different infections.…”
Section: Discussionmentioning
confidence: 59%
“…As in the case reported, antifungal therapy requires adjunct debridement surgery to treat the lesions [1,6,10]. However, topical and systemic antifungal therapy has been reported to be effective in some cases, especially if it includes natamycin [7] and azoles (voriconazole, itraconazole) [8].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a clinical case reported by Monden et al, topical and intravenous administration of micafungin was found to be effective and safe in the treatment of fungal keratitis due to Pestalotiopsis clavispora after prior treatment with topical voriconazole and pimaricine in recurrence of infection [ 72 ]. Micafungin in combination with voriconazole has been shown to be effective in treating fungal keratitis caused by Beauveria bassiana when treatment with topical and systemic voriconazole and topical natamycin has not yielded favorable clinical results [ 73 ]. Treatment success was attributed to the synergistic effect of voriconazole and micafungin and surgical clearance.…”
Section: Discussionmentioning
confidence: 99%